Perioperative Registered Nurses are Essential To Quality Patient Care In The Operating Room Mission Statement - ORNAC, ORNAC (Operating Room Nurses Association of Canada Journal, 1998)
The scope of Perioperative Nursing practice is a continuum ranging from a basic to an advanced level of professional nursing that focuses on identifying and meeting the individual needs of the surgical patient immediately preoperatively, intraoperatively, and immediately postoperatively.